2018
DOI: 10.15252/embr.201846085
|View full text |Cite
|
Sign up to set email alerts
|

Dual localized kinesin‐12 POK 2 plays multiple roles during cell division and interacts with MAP 65‐3

Abstract: Kinesins are versatile nano-machines that utilize variable non-motor domains to tune specific motor microtubule encounters. During plant cytokinesis, the kinesin-12 orthologs, PHRAGMOPLAST ORIENTING KINESIN (POK)1 and POK2, are essential for rapid centrifugal expansion of the cytokinetic apparatus, the phragmoplast, toward a pre-selected cell plate fusion site at the cell cortex. Here, we report on the spatio-temporal localization pattern of POK2, mediated by distinct protein domains. Functional dissection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 65 publications
(205 reference statements)
0
54
0
Order By: Relevance
“…PAKRP1/Kin12A and PAKRP1L/Kin12B belong to class II and regulate the organization of the phragmoplast during male sporogenesis [26,27,28]. The class I proteins POK1/Kin12C and POK2/Kin12D mediate accurate cell plate positioning (Figure 1) [6,7,8,12]. Although Kin12E (encoded by At3g44050 , class I, Figure 1) and Kin12F (encoded by At3g20150 , class II, Figure 1) have not yet been characterized, transcript profiling revealed that both are upregulated during mitosis, suggesting a cell division-related role [29].…”
Section: Plant Kinesin-12: An Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…PAKRP1/Kin12A and PAKRP1L/Kin12B belong to class II and regulate the organization of the phragmoplast during male sporogenesis [26,27,28]. The class I proteins POK1/Kin12C and POK2/Kin12D mediate accurate cell plate positioning (Figure 1) [6,7,8,12]. Although Kin12E (encoded by At3g44050 , class I, Figure 1) and Kin12F (encoded by At3g20150 , class II, Figure 1) have not yet been characterized, transcript profiling revealed that both are upregulated during mitosis, suggesting a cell division-related role [29].…”
Section: Plant Kinesin-12: An Overviewmentioning
confidence: 99%
“…During phragmoplast expansion towards the cell cortex, microtubules polymerize at its leading edge and depolymerize from the central lagging zone upon vesicle fusion and cell plate biosynthesis (Figure 3) [32]. Arabidopsis PAKRP1/Kin12A and PAKRP1L/Kin12B as well as POK2/Kin12D emerge during late anaphase and label the midzone of the phragmoplast until its disassembly at the end of cytokinesis (Figure 2 and Figure 3) [7,27]. Immunolocalization experiments also show OsKINESIN12A at the phragmoplast midzone in rice [22], supporting the notion that the association with the midzone might be a common feature of kinesin-12; although this requires further investigation.…”
Section: Plant Kinesin-12: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations